SARS-CoV-2 Positive and Isolated at Home: Stress and Coping Depending on Psychological Burden - Kowalski, Elias; Schneider, Axel; Zipfel, Stephan; Stengel, Andreas; Graf, Johanna (Frontiers in Psychiatry, 2021)
Objective: The SARS-CoV-2 pandemic has led to pronounced health changes, especially for those infected and psychologically burdened. This cross-sectional study examined the stress experience and coping strategies during home isolation of SARS-CoV-2 infected individuals and analyzed differences regarding psychological burden. Methods: SARS-CoV-2 infected respondents were recruited by telephone and completed an online survey during their home isolation. This questionnaire assessed sociodemographic aspects, somatic factors, psychological burden (depressive symptoms, anxiety, somatic symptom disorder), perceived stress and coping behavior during the home isolation. Results: Out of 838 SARS-CoV-2 infected individuals during the study period, 648 were contacted and 224 home-isolated respondents were included in the study. Disgrace, social restrictions, job fear, health concerns, and infectiousness could be explored as stressors during the home isolation. 54% experienced psychological burden. SARS-CoV-2 infected and home-isolated individuals with psychological burden perceived significant stressors more strongly (p < .001, r = .5) and coped significantly less (p < .001, r = .3) with their infection and home isolation compared to SARS-CoV-2 infected individuals without psychological burden. Conclusion: SARS-CoV-2 infected individuals with psychological burden experienced higher stressors and were unable to cope adaptively with home isolation. Therefore, a general and standardized screening procedure for psychological burden should be established. SARS-CoV-2 infected individuals with psychological burden should receive targeted support with professional help in the areas of stress experience and coping skills during their home isolation and beyond to avoid long-term consequences.